Framing Of Climate Change Impacts And Use Of Management Accounting Practices - Kumarasiri, Jayanthi; Jubb, Christine (Asian Academy of Management (AAM), 2017)
This study examines (i) how companies perceive climate change impacts in terms of opportunities or threats and the reasons for these perceptions, and (ii) use of management accounting practices to manage carbon emissions and the relationship between climate change perceptions and accounting use. The sample consists of Australian companies that participated in the Carbon Disclosure Project (CDP) 2009 survey. We fnd that how climate change impacts are framed (as threat or opportunity) inﬂuences the use of planning and target setting, performance measurement and incentivisation in managing emissions. However, in general, use of accounting practices in managing carbon emissions is limited.